THE USE OF “MISS PEREGRINE’S HOME: FOR PECULIAR CHILDREN” MOVIE AS A MEDIA TO TEACH WRITING RECOUNT TEXT IN TENTH-GRADE STUDENTS (RETAIN, 2020)
The aim of this article is to know how movie is used in teaching writing and to find out the students’ opinion about the use of movie in learning to write a recount text. Writing skill has become one of important role in English language. Unfortunately, teachers still use a conventional method in some areas. In the learning activity, media is divided into three kinds, those are; visual media, audio media and audio visual media. The teacher should offer interesting media to attract the learner’s attention. By using the movie, it is expected that the learners will pay attention to the teacher and the lesson. This research was done qualitatively using case study. This study was conducted in classroom. The subject of this study was a teacher of a senior high school in Gresik and her tenth grade students. The data were collected through observation and interview by using field note and questionnaire as the research instruments. The result of this study showed that there are three steps of implementation of movie as a media to teach recount text namely previewing, viewing, and post viewing. Besides, the result also showed that according to the questionnaire, the students stated that the use of movie could help the student’s learn to write a recount text.